Konstrukce autosalonu v Kyjově - Devetterová, Monika (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Bakalářská práce se zabývá návrhem nosných prvků a posouzením únosnosti a použitelnosti nosné konstrukce objektu autosalonu. Autosalon pro 10 vystavených vozidel v Kyjově má navržené půdorysné rozměry 30 m x 24 m a je vysoký 8,24 m. Nosná konstrukce je navržena z lepeného lamelového dřeva v kombinaci s ocelí. Opláštění budovy tvoří velkoformátové panely systému Novatop. Nosná konstrukce je tvořena sedmi rámovými vazbami a je doplněna ztužením. Konstrukce je vymodelována jako prutový 3D model v programu Dlubal RFEM. Spoje jsou posouzeny dle ČSN EN 1995-1-1.

Bachelor´s thesis focuses on the design of load-bearing elements and the assessment of the load-bearing capacity and usability of the load-bearing structure of a car showroom building. The car showroom for 10 exhibited vehiclesis located in Kyjov and has designed plan dimensions of 30 m x 24 m with a height of 8,24 m. The load-bearing structure is designed using glued laminated timber in combination with steel elements. The building envelope consists of large-format panels of the Novatop system. The load-bearing structure consists seven frame connections and is supplemented with bracing elements. The structure is modeled as a 3D member model in Dlubal RFEM software. The joints are assessed according to ČSN EN 1995-1-1.
Construction of a Car Showroom in Kyjov
Keywords: Dřevěné konstrukce; ocelové konstrukce; lepené lamelové dřevo; trojlodní střecha; Novatop OPEN; svorníkový spoj; čepový spoj; Timber constructions; steel constructions; glued laminated timber; three-aisled roof; Novatop OPEN; bolt connection; dowel-type connection